2012
DOI: 10.4103/2156-7514.92372
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Imaging Features of Fasciola hepatica Infection – A Pictorial Review

Abstract: Fascioliasis refers to a zoonosis caused by Fasciola hepatica, a trematode infecting herbivores, but also occurs in humans who ingest the metacercaria found in fresh water plants. Infection in humans is common in developing countries and is also not uncommon in Europe. Diagnosis of this infection is difficult, as the history and symptoms are nonspecific and stool analysis for eggs is negative until the disease is in an advanced state by when the parasite has reached the biliary system. The clinical course cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 9 publications
(16 reference statements)
3
72
0
8
Order By: Relevance
“…Enlarged porta hepatis nodes are visible in 51% on US or CT (93) . Biliary abnormalities are present in 45% of cases and may include visible parasites in the gallbladder or bile ducts, or biliary duct dilatation, thickening, oedema or abnormal enhancement (93,95) . After eight weeks ductal ectasia may be seen with bile duct thickening, dilatation and tortuosity occurring after 12 weeks (95) .…”
Section: Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Enlarged porta hepatis nodes are visible in 51% on US or CT (93) . Biliary abnormalities are present in 45% of cases and may include visible parasites in the gallbladder or bile ducts, or biliary duct dilatation, thickening, oedema or abnormal enhancement (93,95) . After eight weeks ductal ectasia may be seen with bile duct thickening, dilatation and tortuosity occurring after 12 weeks (95) .…”
Section: Imagingmentioning
confidence: 99%
“…Biliary abnormalities are present in 45% of cases and may include visible parasites in the gallbladder or bile ducts, or biliary duct dilatation, thickening, oedema or abnormal enhancement (93,95) . After eight weeks ductal ectasia may be seen with bile duct thickening, dilatation and tortuosity occurring after 12 weeks (95) . Other findings include mild splenomegaly, ectopic inflammation in the abdominal wall or bowel (93) .…”
Section: Imagingmentioning
confidence: 99%
“…The highest prevalence was found in Bolivia, where stool examination revealed a prevalence of 72%, and serologic tests were positive in 100%. 8,9 Lopez et al investigated the prevalence of Fasciolosis in school age children in Peru and they reported that 10.3% had positive stool microscopy. 10 There have been several epidemiologic studies on Fasciolosis in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…Biliary parasitosis may lead to a series of complications such as obstructive jaundice, pyogenic cholangitis, acute pancreatitis, intrahepatic stones, liver abscesses, acute or chronic cholecystitis, and even cholangiocarcinoma and hepatocellular carcinoma [1 -3]. Imaging techniques such as ultrasound, computed tomography, and MRCP are usually non-specific [4]. Only the serology and identification of ova in the stool or duodenal aspirates are specific, but not routinely done in clinical practice [1].…”
mentioning
confidence: 99%